1989
DOI: 10.2165/00003088-198900161-00004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Disposition of Quinolones in Human Body Fluids and Tissues

Abstract: The unique pharmacokinetic properties as well as the body fluid and tissue penetration of quinolones are discussed.Quinolones are well absorbed from the gastrointestinal tract and are eliminated with considerable d{fJerences in their terminal half-lives. The major elimination pathways of quinolones are renal excretion and hepatic metabolism. Renally. these drugs undergo the potential excretion mechanisms (glomerular filtration. tubular secretion. reabsorption). In the liver. they are metabolised primarily by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
9

Year Published

1992
1992
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 45 publications
2
40
0
9
Order By: Relevance
“…On the other hand, the fluoroquinolone antibiotics have been demonstrated to show extensive distribution and good penetration of the extravascular compartment (8,15,18,19,21). This characteristic is probably due to their low protein binding, high lipophilicity, and relatively small molecular size.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the fluoroquinolone antibiotics have been demonstrated to show extensive distribution and good penetration of the extravascular compartment (8,15,18,19,21). This characteristic is probably due to their low protein binding, high lipophilicity, and relatively small molecular size.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this assessment, ciprofloxacin has been classified as a low-permeability compound (Volpe, 2004;Zakelj et al, 2006). In vivo it displays variable oral bioavailability of between 50 and 80% (Sörgel et al, 1989a). Ciprofloxacin plasma clearance in vivo is predominantly renal (Jaehde et al, 1989;Rohwedder et al, 1990), but it is also subject to intestinal elimination (Sörgel et al, 1989b(Sörgel et al, , 1991 without undergoing significant metabolism (Sörgel et al, 1989b).…”
Section: Introductionmentioning
confidence: 93%
“…Penetration into the CNS is relatively good, and vitreous humor penetration is approximately 20% (Barza, 1991). Apart from nasal secretions (Dobbs et al, 1988) and ejaculate, body fluid concentrations of fluoroquinolones rarely reach plasma concentrations (Sorgel et al, 1989). Thus, the high tissue concentrations are a result of sequestration onto, or within, cells or cellular components of a tissue, although Carlier et al (1990) found no specific subcellular structure affinity to pefloxacin.…”
Section: Pharmacokineticsmentioning
confidence: 99%